2022
DOI: 10.1111/1759-7714.14592
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping of cerebrospinal fluid in lung cancer patients with leptomeningeal metastasis

Abstract: Background: The prognosis of non-small-cell lung cancer (NSCLC) with leptomeningeal metastasis (LM) is poor. Detection of cell-free DNA (cfDNA) by next generation sequencing (NGS) in cerebrospinal fluid (CSF) may facilitate diagnosis of LM and identification of drug resistance mechanisms, yet its clinical use needs to be further verified. Methods: We performed a retrospective cohort study to assess the genetic profiles of paired CSF and plasma samples in lung cancer patients with LM. Of 17 patients screened, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…What's more, we demonstrated that CSF ctDNA has a signifcantly higher detection rate than plasma. This result is consistent with previous study which show that CSF ctDNA exhibite a more comprehensive genetic landscape than plasma of CNS metastases [14,16,17,19]. Previous studies have compared the detection rate of EGFR and found that it is higher in CSF than plasma.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…What's more, we demonstrated that CSF ctDNA has a signifcantly higher detection rate than plasma. This result is consistent with previous study which show that CSF ctDNA exhibite a more comprehensive genetic landscape than plasma of CNS metastases [14,16,17,19]. Previous studies have compared the detection rate of EGFR and found that it is higher in CSF than plasma.…”
Section: Discussionsupporting
confidence: 93%
“…CSF ctDNA exhibit unique genetic pro es and distinct resistance mechanisms during treatment in NSCLC patients with brain metastases, so it is crucial to test for acquired resistance at CNS progression [13,14]. ctDNA is more abundantly present in the CSF than in plasma and has been shown as a biomarker of treatment effect and tumor evolution in patients with LM [15][16][17]. In order to fully explore the effectiveness of CSF ctDNA representing genetic information in LM versus that of plasma ctDNA in our study, we compared the matched CSF and plasma from the same LM patients.…”
Section: Introductionmentioning
confidence: 99%
“…Recent cohort studies have demonstrated the feasibility of detecting CSF-tDNA in patients with EGFR-mutant and ALK-rearranged NSCLC. [27][28][29][30][31][32][33][34][35][36][37] Consistent observations across these reports are higher variant allele fractions (VAFs) in CSF compared to plasma and better concordance between the original tumor and CSF-tDNA, than between tumor and plasma ctDNA. Preliminary results suggest the sensitivity of CSF-tDNA is superior to that to CSF cytology 23 and the utility of CSF-tDNA to predict treatment response remains unknown.…”
Section: Introductionmentioning
confidence: 60%